2021
DOI: 10.1038/s41598-021-01372-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sutureless securement on hemodialysis catheter-related bloodstream infection

Abstract: The use of sutureless securement devices during catheterization might reduce the risk of catheter-related bloodstream infection (CRBSI) by suppressing catheter-exit infection and catheter dislodgement. However, the effectiveness of these devices in reducing CRBSI risk when securing hemodialysis catheters has not been explored. This single-center retrospective observational study examined 211 non-tunneled hemodialysis catheters (NTHCs) from 110 hemodialysis inpatients, of which 121 were secured using convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Fujimoto et al conducted a retrospective cohort study in 2021 that compared the performance difference between traditional skin sutures and GRIP-LOK devices, a sutureless securement device. They found that the GRIP-LOK device was more effective than traditional skin sutures at preventing catheter-related bloodstream infections, catheter site exit infections, and catheter dislodgment in patients using a non-tunneled hemodialysis catheter [ 29 ]. Due to the better performance and decreased risk that is seen with the use of sutureless adhesive devices, the use of sutures for catheter securement has decreased [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Fujimoto et al conducted a retrospective cohort study in 2021 that compared the performance difference between traditional skin sutures and GRIP-LOK devices, a sutureless securement device. They found that the GRIP-LOK device was more effective than traditional skin sutures at preventing catheter-related bloodstream infections, catheter site exit infections, and catheter dislodgment in patients using a non-tunneled hemodialysis catheter [ 29 ]. Due to the better performance and decreased risk that is seen with the use of sutureless adhesive devices, the use of sutures for catheter securement has decreased [ 12 ].…”
Section: Reviewmentioning
confidence: 99%